Cervantes, educador, consejero y buen amigo - Verdín Díaz, Guillermo (Didáctica. Lengua y Literatura, 2006)
When somebody teaches offering pleasure and instruction, as Cervantes does in his masterpiece Don Quixote, it is not difficult to see him as the educator, the advisor and the friend.While the first two qualities are obvious, the third, that of the friend, can be inferred from the other two. When an educator emphasizes and enthusiastically searches for the truth, he automatically becomes a good and life long friend. For Cervantes —in keeping with the humanistic moral philosophy— the truth, the deep profound truth, takes root in th virtue, the basis of the human perfection. Here in lies the vital importance of the advice for the body and soul.